Development A Constructivist Module and Web on Circle and Sphere Material with Wingeom Software - Hamdunah Hamdunah; Alfi Yunita; Zulkardi Zulkardi; Muhafzan Muhafzan (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2016)
This research aims to develop constructivist module and web on circle and sphere material with wingeom software are valid, practice and effective. The type of this research is development research. This research constitute development research utilize Plomp design that comprise of three phases: 1) the preliminary research, 2) prototyping phase, and 3) assessment phase. The research results obtained constructivist module and web on circle and sphere material with software wingeom are 1) valid in aspects of content, presentation, linguistic and kegrafikaan, 2) practice in the aspect of easy to use, efficient time and benefit, 3) effective based on the results of the final test student of mathematics education in STKIP PGRI West Sumatra on circle and the sphere material.Keywords: constructivist module, the web, circle and sphere, software WingeomÂ DOI: http://dx.doi.org/10.22342/jme.7.2.3536.109-116